Morphologic Segmentation Linearity in Jose Garcia Villa's PROEM - Jett C Quebec (JETAL: Journal of English Teaching & Applied Linguistic, 2022)
Morphology is the study of the intertwined relationship of morphemes, or what we commonly refer to as "words.". Analysis of words enables us to experience how to break apart unfamiliar words in order to understand their overall meanings. It aids us in understanding how prefixes and suffixes can change a word's meaning and how much of our language is constructed. This paper aims to analyze morphologically the textuality of the poem Proem by Jose Garcia Villa by describing the segmentation of the content and function words in the textuality of the poem PROEM focusing on the affixation structuration of the lexical and grammatical morphemes. The linear morphologic segmentation of morphemic contents of the poem "PROEM" by Jose Garcia Villa reveals nineteen lexical morphemes. There are ten (10) simple form (roots), seven (7) complex forms (affixations and roots), one (1) compound form (two roots combined), and one (1) compound–complex form (two roots combined and affixation). On the other hand, there are seven (7) grammatical morphemes of three prepositions, two determiners and two conjunctions. It further reveals that words undergo changes in terms of their class after going through the process of affixation. The results prove that the poem "Proem" by Jose Garcia Villa follows morphologic segmentation linearity in its free verse textuality. This study thus recommends that a parallel morphological investigation be conducted on different textualities of poetry used and read by teachers and students in the process of academic discourse.